Systematic review of knowledge, attitude, and practices regarding dengue in Malaysia - Ajibola, Lamidi-Sarumoh Alaba; Shohaimi, Shamarina; Adam, Mohd Bakri; Mohd Nadzir, Mohd Noor Hisham; Segun, Oguntade Emmanuel (Journal of Applied Pharmaceutical Science, 2018)
Several studies had focused on assessing the relationship and description of the level of knowledge, attitude, and preventive practices (KAP) regarding dengue in Malaysia among different districts, different set of people living in rural, semi-urban, and urban areas over the years. This study reviewed the behavioral evidence, differences, and similarities of the KAP studies despite the use of different instruments for data collection and methodologies for the analysis of data. The search for the literature was conducted in January 2018 via the electronic database of PubMed, Scopus, Science Direct, EBSCOhost, ProQuest, and Google Scholar. Open access journals that were published between June 1986 and December 2017 were examined, focusing mainly on Malaysia as a country. Seventeen articles met the inclusion benchmarks. Most studies showed that the high level of knowledge influences good attitude and high preventive practices. Knowledge was mostly attributed to some socio-demographic factors. It is essential to compile the KAP studies regarding dengue which are done in different locations/districts of a country over the years, in order to project into the future on how to disseminate information to mitigate dengue infection and also to know the most influencing factors affecting it.